2005
DOI: 10.1371/journal.pmed.0020112
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV-1 Subtype and Antiretroviral Therapy on Protease and Reverse Transcriptase Genotype: Results of a Global Collaboration

Abstract: BackgroundThe genetic differences among HIV-1 subtypes may be critical to clinical management and drug resistance surveillance as antiretroviral treatment is expanded to regions of the world where diverse non-subtype-B viruses predominate.Methods and FindingsTo assess the impact of HIV-1 subtype and antiretroviral treatment on the distribution of mutations in protease and reverse transcriptase, a binomial response model using subtype and treatment as explanatory variables was used to analyze a large compiled d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
256
2
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(272 citation statements)
references
References 48 publications
11
256
2
3
Order By: Relevance
“…As reported recently [Kantor et al, 2005], HIV-1 subtypes differ from one another by 10%-12% in nucleotide sequence and only 5%-6% in amino acid sequence in protease and reverse transcriptase genes. Furthermore, some observations suggest that HIV-1 non-B subtypes respond differently to certain antiretroviral drugs (see references 27-35 in [Kantor et al, 2005]). Hence, high sequence conservation does not necessarily indicate low (i.e., predictable) biological variability.…”
Section: Biological Relevance Of Gbv-c Genotypessupporting
confidence: 54%
“…As reported recently [Kantor et al, 2005], HIV-1 subtypes differ from one another by 10%-12% in nucleotide sequence and only 5%-6% in amino acid sequence in protease and reverse transcriptase genes. Furthermore, some observations suggest that HIV-1 non-B subtypes respond differently to certain antiretroviral drugs (see references 27-35 in [Kantor et al, 2005]). Hence, high sequence conservation does not necessarily indicate low (i.e., predictable) biological variability.…”
Section: Biological Relevance Of Gbv-c Genotypessupporting
confidence: 54%
“…81,82 Overall, it appears that most antiretroviral resistance in non-B subtypes is accounted for within the current resistance databases. 83 Further studies of treated cohorts infected with non-B HIV-1 are needed to determine whether other subtype-specific pathways to resistance exist (Table 3).…”
Section: Emergence Of Resistance To Antiretroviral Therapymentioning
confidence: 99%
“…49 A 2005 meta-analysis of 3686 persons with non-B subtypes and 4769 with B subtypes found that 55 known treatmentassociated mutations that were observed in subtype B were also found in non-B subtypes, and the converse was true for 61/67 mutations observed in non-B subtypes. 50 In contrast, a study by Palma et al in 2009 found that genetic background played a role in different treatment-associated mutations that developed in subtypes B and G in Portuguese patients. 51 In a study of patients from Rio Grande do Sul, Brazil, in a population infected by subtypes B and C, a lower rate of accumulation of mutations was found in subtype C than subtype B.…”
Section: Hiv-1 Subtype On Drug Resistance Mutations In Nigeriamentioning
confidence: 94%